2011
DOI: 10.1152/jn.00070.2011
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia-induced sensitization of central chemoreceptors contributes to sympathetic nerve activity during late expiration in rats

Abstract: Molkov YI, Zoccal DB, Moraes DJ, Paton JF, Machado BH, Rybak IA. Intermittent hypoxia-induced sensitization of central chemoreceptors contributes to sympathetic nerve activity during late expiration in rats. J Neurophysiol 105: 3080 -3091, 2011. First published April 6, 2011 doi:10.1152/jn.00070.2011.-Hypertension elicited by chronic intermittent hypoxia (CIH) is associated with elevated activity of the thoracic sympathetic nerve (tSN) that exhibits an enhanced respiratory modulation reflecting a strengthened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
184
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(194 citation statements)
references
References 79 publications
(84 reference statements)
9
184
0
1
Order By: Relevance
“…Expression is also observed in downstream sympathetic regulatory cell groups, including neurons in the hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla (8,27). Importantly, full expression of hypertension in our 7-day CIH model critically depends on activator protein-1 transcriptional regulation of MnPO neurons by FosB/⌬FosB (8).These and other observations (7,9,40,41,46,70) indicate that exaggerated SNA and the neurogenic component of CIHinduced hypertension are complex and might not arise solely from the sensitization of arterial chemoreceptors. In the present study, we sought to determine the early contribution of forebrain/hypothalamic neural mechanisms in hypertension induced by 7 days of CIH.…”
supporting
confidence: 54%
“…Expression is also observed in downstream sympathetic regulatory cell groups, including neurons in the hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla (8,27). Importantly, full expression of hypertension in our 7-day CIH model critically depends on activator protein-1 transcriptional regulation of MnPO neurons by FosB/⌬FosB (8).These and other observations (7,9,40,41,46,70) indicate that exaggerated SNA and the neurogenic component of CIHinduced hypertension are complex and might not arise solely from the sensitization of arterial chemoreceptors. In the present study, we sought to determine the early contribution of forebrain/hypothalamic neural mechanisms in hypertension induced by 7 days of CIH.…”
supporting
confidence: 54%
“…The altered control of expiratory activity of CIH rats seems to contribute significantly to increase baseline sympathetic activity in these animals (58). This is supported by our findings obtained in in situ preparations showing that the higher levels of sympathetic activity of CIH-treated rats are, in part, entrained with the emergence of high-amplitude bursts in abdominal expiratory motor activity (43,57,60). Furthermore, it has been reported that CIH rats exhibited exaggerated sympathoexcitatory and phrenic responses to a new hypoxic challenge (14,26,38,42), indicating a facilitation of the processing of hypoxic reflex responses.…”
supporting
confidence: 69%
“…Accumulating evidence suggests that the central mechanisms underpinning sympathetic overactivity associated with CIH exposure involve plastic changes in the neuronal circuitries modulating both sympathetic and respiratory functions (43,57,60). The present study provides neurochemical evidence that glutamatergic neurotransmission is increased in the cNTS of rats submitted to CIH.…”
Section: Perspectives and Significancesupporting
confidence: 53%
“…Considering the increase in the respiratory frequency after KYN microinjected into the RVLM/BötC, we suggest that bilateral microinjections of KYN into the BötC decreased pontine/RTN excitatory inputs to post-I and aug-E BötC neurons, changing the basal respiratory pattern to the observed abnormal pattern characterized by an increase in the respiratory frequency due to a decrease in the duration of inspiration and expiration. This change probably occurred because the pre-I neurons received inhibitory inputs from aug-E neurons (controlling the pre-I activity), whereas ramp-I received inhibitory inputs from post-I (controlling the duration of inspiration and expiration) (Hayashi et al 1996;Molkov et al 2011;Rybak et al 2008). Microinjections of KYN into the RVLM/BötC decreased the inhibitory tonus from BötC post-I and aug-E neurons to preBötC inspiratory neurons, allowing a decrease in the duration of expiration and an increase in the activities of pre-I neurons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expiratory activity during baseline seems to be generated mainly by expiratory neurons of BötC (Ezure et al 2003a,b,c;Tian et al 1999) while during high respiratory drive, such as in conditions of hypercapnia/hypoxia, a distinct expiratory generator located at the retrotrapezoid/parafacial respiratory group (RTN/pFRG) is activated and plays a critical role in the generation of active expiration (Abdala et al 2009;Molkov et al 2010Molkov et al , 2011. Intermingled with the BötC and pre-BötC neurons are the presympathetic neurons of the RVLM, which anteroposterior distribution is as long as 700 m from the caudal end of the facial nucleus to the caudal ventrolateral medulla (CVLM) (Dobbins and Feldman 1994;Wang et al 2002Wang et al , 2009).…”
mentioning
confidence: 99%